Experience and Consequences of Happiness: A Study of Happiness among School Students and Teachers - Srivastava, Ashok K.; Misra, Girishwar (INDIAN EDUCATIONAL REVIEW, 2013)
The pursuit of happiness is an ever continuing process in all societies. The experience of happiness affects the personal, socio-emotional, and task performance of the people. The societies, however, differ in their conceptualisation of happiness. In individualistic societies more importance is given to personal traits and achievements of the individuals in their conceptualisation. The collectivistic societies, in contrast, view happiness resulting from positive social relationships and task performance. The Indian sub-continent offers a pluralistic vision on knowledge and reflects diversity in viewing reality. The Indian way of thinking is characterised as context sensitive and operates with abstract generalisation and universal categories. The Indian perspective on reality and human functioning is holistic, recognises coherence and natural order across all life forms, emphasises self-discipline, and gives dharma as the sacred moral code. In particular, the study examined the Indian notion of happiness using multiple resources. Also, the perception of school students and teachers on happiness as well as strategies adopted by them to be happy in life and promote happiness in others were explored.